The Prevalence of Cardiovascular Abnormalities in Thyrotoxicosis A Cross Sectional Study - Kudan, Sonika; Lal, Mohan; Angral, Rajesh (Journal of Medicine, 2015)
Background: In this Cross sectional study over a period of one year, conducted in the Division of Cardiology, Dept. of Medicine, Govt. Medical College Hospital Jammu, a total of 50 cases were studied for cardiovascular abnormalities occurring in thyrotoxicosis. Aims: We investigated the prevalence and clinical importance of cardiovascular abnormalities in patience with thyrotoxicosis. Settings and Design: This is a cross sectional study conducted over a period of one year in a tertiary care hospital offering specialty and super specialty including cardiology. We studied 50 cases of whom 11 were males and 39 were females. The study covered age group with a range of 16 years to 85 years. Methods and Material: All newly diagnosed cased of thyrotoxicosis were included in the study and were evaluated on a protocol which includes: history, general physical examination, cardiovascular examination and investigation: bio chemical profile, hormonal assay, chest radiography, twelve lead electrocardiogram (ECG), Echocardiography (ECHO) (M-Mode/2 dimensional/Colour Doppler). Statistical Analysis: Descriptive analysis including calculation of percentages as deemed fit for qualitative variables. For quantitative variables, mean and standard deviation were calculated and reported. Results: 50 patients (Mean [+/- SD] age, 45.7 yrs, range 16-85 yrs; 78% females) were included. Weakness and fatigability was present in every patient (100%), followed by palpitation, shortness of breath and weight loss (94%). We found ventricular hypertrophy (40%), congestive heart failure (CHF) (36%), cardiomegaly (24%), arrhythmias (24%) and bundle branch block (18%) of the patients. Conclusion: Cardiovascular abnormalities in thyrotoxicosis should never be over looked, prognosis and outcome of the heart disease depends on early institution of treatment and control of the hormone levels. J MEDICINE July 2015; 16 (2) : 69-72